Mental Health on Suicide Idea in Students Akper Karya Bhakti Nusantara Magelang (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
This study explores the relationship between mental health and suicidal ideation among students of Akper Karya Bhakti Nusantara Magelang. Mental health is a crucial component of overall well-being, especially for teenagers. The rising phenomenon of suicide among students has raised concerns regarding its link to mental health disorders. Mental health problems significantly contribute to the emergence of suicidal ideation, and this study aims to examine how mental health impacts the occurrence of suicidal thoughts in students. A quantitative correlation research design with a cross-sectional approach was employed. The study's sample consisted of 178 students from levels I, II, and III of the Karya Bhakti Nusantara Nursing Academy, with the majority of respondents being female (79.21%) and the highest proportion of students in level III (40.4%). According to the findings, 91.0% of students reported having normal mental health, while 9.0% showed signs of mental health disorders. Regarding suicidal ideation, 85.4% of students reported weak suicidal thoughts, while 14.6% exhibited moderate to large ideas of suicide. Statistical analysis revealed a significant correlation between mental health and suicidal ideation with a p-value of 0.000. The strength of the correlation was found to be low (0.259), indicating a positive but weak association between the two variables. This study concludes that students' mental health is significantly related to their level of suicidal ideation. The findings emphasize the need for mental health support and intervention for students to prevent the escalation of suicidal thoughts, increase awareness, and improve overall well-being. Mental health services and counseling should be incorporated into academic environments to create supportive, proactive measures.